Risk of Developing Heart Rhythm Disturbances in Arterial Hypertension - Nuritdinova Nigora Batirovna; Shukurjanova Surayo Makhmudovna; Khasanova Nelya Alibaevna (Scientific Trends, 2025)
This article highlights the problem of arterial hypertension from a scientific, theoretical and practical point of view. Arterial hypertension is diagnosed by daily blood pressure monitoring. With arterial hypertension, there is a frequent violation of the heart rhythm. The importance of Holter ECG monitoring in arterial hypertension is considered. With arterial hypertension, it is necessary to carry out daily monitoring of blood pressure to diagnose, determine the type of hypertension, and evaluate the effectiveness of hypertension treatment. In case of arterial hypertension accompanied by rhythm disturbances, Holter ECG monitoring is prescribed.
Keywords: Arterial hypertension, diagnosis, daily blood pressure monitoring, Holter ECG monitoring, cardiac arrhythmia.